Current Situation and Key Parameters for Improving Wheat Quality in China - Ma, Mingming; Li, Yingchun; Xue, Cheng; Xiong, Wei; Peng, Zhengping; Han, Xue; Ju, Hui; He, Yong (Frontiers in Plant Science, 2021)
Processing quality of winter-wheat is affected by genotype, environmental conditions as well as crop husbandry practices. In the present study, a data set of 17 quality-related traits for 211 main winter-wheat varieties in China during 2006 to 2018 was extracted from China Wheat Quality Report. Analysis was carried out to evaluate the quality status and variations, to reveal correlation between quality-related traits as well as to identify key influencing factors. Results indicated that the quality indicators of weak- and strong-gluten wheat varieties were acceptable, while those of weak- and strong-gluten wheat varieties were far below national standard, especially hardness index (HI), crude protein content (CPC), wet gluten content (WG) and water absorption (WA) for weak-gluten wheat and sedimentation value (SV), stability time (ST) and stretch area (SA) for strong-gluten wheat, respectively. Correlation analysis showed that CPC, SV and WG had no significant correlation with the processing quality of noodles score, while gluten index (GI) significantly correlated with noodle score (p < 0.001). This implied that protein quality might play a more important role than protein quantity in determining medium-gluten wheat quality. Furthermore, analysis of variance showed that genetic characteristics (cultivars) had significant influences on the restriction indexes (SV, ST and SA) of strong-gluten wheat, while genetic characteristics, environment conditions and crop growing practices (cultivars, locations and years) significantly affected the restriction indexes (HI, CPC, WG and WA) of weak-gluten wheat. The results suggest that improvement of Chinese strong-gluten wheat should mainly focus on cultivating new varieties. As to weak-gluten wheat, cultivation and husbandry practices should be paid more attention to limit undesired high grain protein content.